Upgrading Low-temperature Steam to Match CO2 Capture in Coal-fired Power Plant Integrated with Double Absorption Heat Transformer. (May 2017) - Wang, Dandan; Liu, Feng; Li, Sheng; Gao, Lin; Sui, Jun
Abstract: The energy level mismatch between extraction steam from turbines and heat for CO2 regeneration always results in huge exergy destruction and low thermal efficiency in post combustion power plants with CO2 capture. To solve the problem, a new CO2 capture system driven by a double absorption heat transformer is proposed in this paper. Through the absorption heat transformer, low-temperature steam can be upgraded into high level heat to match the temperature of solvent regeneration. Also, flue gas heat is recovered to preheat the circulating water to further decrease system power penalty. Aspen Plus11.0 is used to simulate the system, and the results of the key process are validated by experimental values. It is shown that with 90% CO2 capture, the thermal efficiency of the proposed system is enhanced by 1.25 percentage points. And the efficiency enhancement of proposed system has a trend of increase first and then decrease with the CO2 capture rate growth. For a 350MW coal-fired power plant, the optimum CO2 capture rate is 53.65% and the corresponding efficiency enhancement is 2.06 percentage points. Exergy analysis shows that due to better match between the upgraded steam and CO2 stripping temperature, the exergy destruction in CO2 separation process of proposed system could decrease by 40.3%, and thereby the exergy efficiency of proposed system is 33.76%, which is 1.85 percentage points higher than the conventional method.